(untitled) (Fiep Bulletin - online, 2020)
This study aimed to analyze the correlation between neck circumference, body mass index (BMI), waist circumference and fat percentage of children enrolled in elementary school in a school in Belém-PA, Brazil. Methodology applied in the research is quantitative, descriptive and cross-sectional, with a 95% confidence level. The present study was conducted on a sample of 100 schoolchildren, 56 boys and 44 girls, aged 8 to 10 years old, attending the 4th year of elementary school, from the Federal Elementary and High School Lieutenant Rêgo Barros, from February to March 2019, in Belém-PA, Brazil. Their guardians signed informed consent forms (ICFs). For statistical treatment, Bioestat 5.0 software was used, performing Pearson correlation coefficient between neck circumference (NC) and BMI, body weight (BW), fat percentage (BFP) and waist circumference (WC) of schoolchildren. There was, as a result, a strong correlation between NC and BW (r = 0.7, p <0.0001), moderate correlations between NC and BMI (r = 0.63, p <0.0001), NC and WC (r = 0.69, p <0.0001) and NC and BFP (r = 0.55, p <0.0001). Therefore, it was observed that neck circumference may be a new biometric marker for assessing child growth, as it has moderate to high correlations with scientifically ratified parameters in the diagnosis of malnutrition or overweight by health professionals